Effects of blended and video-based coaching approaches on preservice teachers' self-efficacy and perceived competence support. (September 2019) - Weber, Kira Elena; Prilop, Christopher Neil; Kleinknecht, Marc
Highlights: Self-efficacy in classroom management (SECM) increased in all groups. V-Coaching+ members' SECM increased significantly more than Live-Coaching members'. Video-based groups reported more competence support than the Live-Coaching group. Video-based self-reflections contained more negative evaluations than peer feedback. Experts provided more balanced (both negative and positive) feedback than novices.